The polyploid Alyssum montanum-A. repens complex in the Balkans: a hotspot of species and genetic diversity - Španiel, Stanislav; Marhold, Karol; Zozomová-Lihová, Judita (Plant systematics and evolution, 2017)
The Balkan Peninsula is an important diversity and speciation centre for many species groups. The high genetic, karyological and morphological complexity of the Alyssum montanum-A. repens species group (Brassicaceae) in the Balkans makes it a challenging study subject for exploring different speciation mechanisms and their taxonomic consequences. In the present study, ploidy level and genetic (AFLPs and chloroplast DNA sequences) data were examined and confronted with recent taxonomic concepts. Remarkable genetic and morphological variation, which is often geographically structured, and high incidence of polyploids suggest a very complex evolutionary history in this area, involving allopatric differentiation and past hybridisation and polyploidisation events. A new taxonomic treatment, differing substantially from recent concepts, is suggested. Several previously recognised taxa, including many endemics, such as A. austrodalmaticum, A. handelii, A. moellendorfianum, A. pirinicum and A. wierzbickii, are confirmed as distinct. Several other taxa are suggested to be resurrected or elevated to the species level, namely, A. bosniacum, A. montenegrinum, A. reiseri and A. vernale. Phylogenetic relationships among populations from the central Balkans and Greece are still partly blurred apparently due to more extensive reticulations, and their taxonomic classifications remain provisional. They are treated here under the tentative name A. spruneri. The patterns of variation revealed in the present study highlight the importance of the Balkan Peninsula for the persistence and diversification of vascular plants.